A novel approach for the synthesis of tin antimony sulphide thin films for photovoltaic application. (March 2015) - Ali, N.; Ahmed, R.; ul Haq, Bakhtiar; Shaari, A.; Hussain, R.; Goumri-Said, Souraya
Graphical abstract: Highlights: Sn–Sb–S are low cost ternary compounds and can replace the existing semiconductors. TAS polycrystallinit has maximum value at 85 °C and 150 °C annealing temperature. Annealing temperature increase results in photoconductivity enhancement of TAS. TAS band gap of 1.6 eV annealed at 150 °C is suitable for photovoltaic. TAS has strong photoconductivity response in the visible and near infrared region. Abstract: Alternative semiconductor materials to copper indium gallium selenide (CIGS), copper zinc tin sulphide (CZTS), cadmium telluride (CdTe) is driven by the need to use less toxic and earth-abundant materials as an absorber layer in thin film solar cells. The ternary compounds based on Sn–Sb–S (TAS) compositions are deemed to be a possible replacement of existing semiconductor materials due to their low processing cost and nontoxic elemental composition. In this study thin films of tin antimony sulphide (TAS) are deposited on glass substrate from tin sulphide and antimony sulphide binary precursors, without substrate heating, combinatorially in thermal vacuum chamber. The average thickness of the library obtained was 1.2 μm as measured by quartz crystal monitor. The X-ray diffraction analyses measured by D-8 Discover diffractometer shows that the as deposited films were amorphous while the annealed films are poly crystalline. The maximum reflection was observed for the lattice plane (1 1 1) for SnSb2 S4 and Sn2 Sb2 S5 . The optical properties of the thin films were measured by ellipsometry while electrical properties were measured by photoconductivity spectrometer and four-probe technique. The band gap was varied with variation in elemental composition as well as annealing temperature between 1.6 and 2.7 eV. It was observed that TAS exhibit bipolar conductivity at different annealing temperature.